3-D DC resistivity modeling and inversion using multi-resolution framework. Issue 1 (1st December 2019) - Gao, Jingyu; Smirnov, Maxim; Smirnova, Maria; Egbert, Gary
Summary: We discuss the implementation of multi-resolution framework to 3-D Direct Current (DC) problem. Commonly used staggered (SG) grid fixes the horizontal grid resolution for all depths. Thus, employing the fine horizontal resolution may lead to an over-discretised forward problem, subsequently affecting the performance of the inversion. We implemented a novel multi-resolution (MR) grid approach to the 3-D DC modeling and inversion problem, which allows adjustment of the horizontal resolution with depth. By using finer resolution for the near-surface regions, MR grid can ensure the modeling accuracy and describe the shallow features in the inversion model as well. The ability to use relatively coarser horizontal resolution for the deeper regions reduces the computation costs compare to the SG grid modeling. As a result, modeling and inversion can be accelerated several times by solving a smaller problem. Our grid resembles non-conformal rectangular grid, which commonly used in finite-elements modelling.